Tingkat Keberdayaan Perempuan Kepala Keluarga (Kasus Pada Program Pekka Di Desa Dayah Tanoh Kecamatan Mutiara Timur Kabupaten Pidie Provinsi Aceh) - Elly Susanti (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
ABSTRACT. Women empowerment is an effort to enhance the capacity of women gaining access and control to economic, politic, social and cultural resources. It is also to strengthen self-development and self-confidence regarding ability to contribute and active participation in the process of decision-making, that reinforce development capability and self-concept. Women headed household empowerment program (Program Pemberdayaan Perempuan Kepala Keluarga PEKKA)aims to cope and deal with any potential women headed household problems comprehensively through community organizing, in particular, related to class and gender inequalities in the community. In order to achieve that objective, the strategy of project management of PEKKA focuses on five pillars, which are participatory, flexibility, mentoring and facilitating, sustainability, and decentralized. This study aims to assess the level of empowerment of women headed household after joining the PEKKA program. The study employs qualitative approach, which is women headed household as a unit analysis. Data gathering was through primary and secondary sources. Primary data collected through participatory observation, in-depth interview, and focus group discussion, meanwhile secondary obtained through project related supportive documents. The process of analysis data was using data reduction, data arrangement and presentation, interpretation, tentative argument and conclusion, and verification. The study shows that the significance of the program encouragingly contributes to empowering women headed household through improvement of wellbeing, opens access to resources, increase critical awareness, as well as participation and control. It is to the greater extent connects to the objective of the program.